Surfactant tunable hierarchical nanostructures of CdIn2S4 and their photohydrogen production under solar light - Bhirud, Ashwini P.; Chaudhari, Nilima; Nikam, Latesh; Sonawane, Ravindra; Patil, Kashinath; Baeg, Jin-Ook; Kale, Bharat (International Journal of Hydrogen Energy, 2011)
The hierarchical nanostructures of CdIn2S4 were selectively prepared through hydrothermal process in the presence of different surfactants. Structural study demonstrated existence of cubic spinel structure and micro structural study shown a pretty marigold flower like morphology without any surfactant. The effect of surfactants on the morphology and microstructure of CdIn2S4 has been studied by using Polyvinyl pyrrolidone (PVP) and Cetyltrimethyl ammonium bromide (CTAB) as a surfactants. The CdIn2S4 bipyramids with length of 0.7-1 mu m have been obtained using PVP. Interestingly, the nanopetals (thin and transparent) of CdIn2S4 are self assembled into hollow spheres in the presence of CTAB. Considering the importance of these unique nanostructures, the growth mechanism has also been proposed. The optical properties demonstrated the band gap in the range of 2.12-2.29 eV which is well within the visible region. In this contest, photocatalytic activity for hydrogen production using the above nanostructures under visible light was also demonstrated. The prima-fascia observations shows that the bipyramidal CdIn2S4 exhibit excellent photocatalytic activity for hydrogen production (3238 mu molh(-1)) than other nanostructures. Being a nanostructured semiconductor chalcogenide with a good stability will also have potential applications in solar cells and LED. Copyright (C) 2011, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Bipyramids; CdIn2S4; Hydrogen generation; hydrothermal; Self-assembled

Hollow nanogold/meso-magnetite composite: pulsed laser synthesis, properties, and biosensing application - Chaudhari, Nilima; Warule, Sambhaji; Agrawal, Shailaja; Thakare, Vishal; Jouen, Samuel; Hannoyer, Beatrice; Kale, Bharat; Paknikar, Kishore; Ogale, Satishchandra B. (Journal of Nanoparticle Research, 2013)
A facile and template-free UV (Excimer) laser photolysis process is demonstrated to transform a Fe-complex into unique hollow Fe3O4 nanosphere morphology with each sphere having nanometric pores and an opening. Depending on the Fe-complex concentration and processing time interesting configurations are seen to evolve. When an identical process is applied to a mixture of Fe-complex and chloroauric acid an enthrallingly decorated Au-Fe3O4 nanostructure evolves, with Au nanoparticles surface-loaded on mesospheric Fe3O4. This room temperature process implemented under normal laboratory conditions is clearly versatile and applicable to heterojunction nanomaterials synthesis in a single-step process. The potential application of these gold-decorated magnetic nanostructures was also investigated for immuno-magnetic capture of E. coli in biosensing and these were found to be sensitive even below 1,000 cfu/ml. The test results demonstrate linear sensing response in the range of 10(3)-10(5) cfu/ml. We also show that these nanostructures can be used for simple electrical conductivity-based biosensing since they show dramatic conductivity change in a simple drop-cast test. A new laser-based approach to the synthesis of unique hollow sphere morphology of magnetite (Fe3O4) without and with Au nanoparticle decoration is presented. The potential application of these gold-decorated magnetic nanostructures was also investigated for immuno-magnetic capture of E. coli in biosensing and these were found to be sensitive even below 1,000 cfu/ml.
Keywords: E. coli cells; Fe-complex; Meso-magnetite; Nanobiotechnology; Nanocomposite; Pulse laser irradiation

Situ preparation of N-ZnO/graphene nanocomposites: excellent candidate as a photocatalyst for enhanced solar hydrogen generation and high performance supercapacitor electrode - Bhirud, Ashwini P.; Sathaye, Shivaram; Waichal, Rupali; Park, Chan-Jin; Kale, Bharat (Journal of Materials Chemistry A, 2015)
We have demonstrated a facile in situ wet chemical method to synthesize nanostructured nitrogen doped ZnO/Graphene (N-ZnO/GR) nanocomposites for the first time. Nitrogen doped ZnO over graphene (N-ZnO/GR) was studied using various concentrations of graphene. During the synthesis of N-ZnO/GR nanocomposites, in situ formation of graphene via GO reduction and formation of 4-9 nm N-ZnO have been demonstrated. The composite N-ZnO/GR absorbs in the visible region and this property is used for the photocatalytic reaction to transform hazardous H2S waste into eco-friendly hydrogen using solar light. The N-ZnO/GR nanocomposite with 0.3% graphene exhibits an enhanced photocatalytic stable hydrogen production rate i.e. similar to 5072 mu mol h(-1) under visible light irradiation. It is noteworthy that the N-ZnO/GR electrode exhibits a high specific capacitance of 555 F g(-1) and excellent cyclic performance with nearly 96.20% capacity retention after 2000 cycles at a current density of 10 A g(-1). These results indicate great potential applications of N-ZnO/GR in developing high hydrogen production and supercapacitors with high energy and power densities.

Ethoxy-ester functionalized imidazolium based ionic liquids for lithium ion batteries - Nirmale, Trupti; Khupse, Nageshwar; Gore, Rohitkumar; Ambekar, Jalindar; Kulkarni, Milind; Varma, Anjanikumar; Kale, Bharat (ChemistrySelect, 2018)
Ethoxy ester functionalized imidazolium and bis(tri fluoromethanesulfonyl)imide based ionic liquids (ILs) are synthesized and considered as electrolyte for lithium ion batteries. The series of ethoxy ester functionalized ionic liquids were chosen with increase in ethoxy unit from one to three, followed by polymeric units. These ionic liquids provide both ester and ethoxy groups as interaction sites for Li+ ions enhancing the Li+ ion transportation, resulting in ionic conductivity of 10(-3) Scm(-1) at 25 degrees C, which is of 10(3) factor higher than ethoxy containing polyethylene oxide solid polymer electrolyte. It's noteworthy that the conductivity increases as ethoxy units are increased from one to three units, followed by a decrease for the polymeric ethoxy unit. Electrochemical stability window of these ionic liquids improves as the ethoxy groups are added to imidazolium cation. The Li/LiFePO4 cell fabricated with [ME(3)AMIm][TFSI] electrolyte shows good initial discharge capacity of 98.5 mAhg(-1) at 0.05 C-rate at room temperature, which gradually decreases with cycling. Systematic investigation of electrode surfaces by using SEM and EDX shows deposition of passivation layers on their surfaces. Ionic liquids fabricated by this facile method provide a promising model system for understanding the molecular interactions in promoting the lithium-ion conduction mechanism. The advantages and the limits associated to series of ionic liquid electrolytes are critically investigated.

Unique N doped Sn3O4 nanosheets as an efficient and stable photocatalyst for hydrogen generation under sunlight - Balgude, Sagar; Sethi, Yogesh; Gaikwad, Aarti; Kale, Bharat; Amalnerkar, Dinesh; Adhyapak, Parag (Nanoscale, 2020)
Unique N doped Sn3O4 nanosheets have been demonstrated successfully using a facile hydrothermal method. Investigations of the triclinic phase and the impurities were performed using powder X-ray diffraction analysis (XRD) and Raman spectroscopy. The morphological analysis demonstrated a rectangular intra- and inter-connected nanosheet-like structure. The length of the nanosheets was observed to be in the range of 200-300 nm and the thickness of the nanosheets was less than 10 nm. The optical study reveals an extended absorption edge into the visible region, owing to the incorporation of nitrogen into the lattice of Sn3O4, which was further confirmed using X-ray photoelectron spectroscopy (XPS). Considering the band structure in the visible region, the photocatalytic activities of pristine and N doped Sn3O4 nanosheets for hydrogen evolution from water under natural sunlight were investigated. 4% N-Sn3O4 showed a higher photocatalytic activity (654.33 mu mol(-1) h(-1) 0.1 g(-1)) for hydrogen production that was eight times that of pristine Sn3O4. The enhanced photocatalytic activity is attributed to the inhibition of charge carrier separation owing to the N doping, morphology and crystallinity of the N-Sn3O4 nanostructures. A stable efficiency was observed for three cycles, which clearly shows the stability of N-Sn3O4.